PULMONARY ASPERGILLOSIS AMONG HIV PATIENTS WITH TB SMEAR NEGATIVE ATTENDING AMINU KANO TEACHING HOSPITAL (FULafia Journal of Science and Technology, 2023)
Aspergillosis is a life threatening disease especially among the immunocompromised, like human immunodeficiency virus (HIV)  infected individuals and Mycobacterium tuberculosis infected patients, whether they are smear positive or negative. The aim of this study was to determine the prevalence of Aspergillosis among HIV patients with TB smear negative results. Early morning sputum samples were collected from HIV patients with TB smear negative results. The samples were screened using Ziehl-Neelsen staining technique before direct Gram’s staining was done and cultured onto Sabouraud Dextrose Agar (DCA) supplemented with chloramphenicol and incubated for 48hrs at 37°C. The fungal isolates were examined morphologically using macroscopy and microscopically identified using lactophenol cotton blue staining under the microscope. One hundred and eighty seven (187) participants were included in the study in which 81(43.3%) were males and 106(56.7%) were females, out of which a prevalence 32(17%) was obtained.
Keywords: Pulmonary aspergillosis; HIV patients; Tuberculosis; Aspergillus species